Semiotics In The Legends Of Mpok Ris As A Character Education Media - Intan Sari Ramdhani; Achmad Hufad; Suroso Mukti Leksono (Peneliti.net, 2022)
Semiotic analysis will be used to explain the legend of Mpok Ris as a character teaching tool. The study of sign systems, such as language, motion, music, and images, is known as semiotics. This study employed a qualitative descriptive research approach, which includes processes for gathering data, recording data, analyzing data, and summarizing research findings. According to Roland Barthes' semiotic approach, the legend of Mpok Ris is employed as a medium for character education by employing the three types of semiotics: denotative, connotative, and mythic. A semiotic analysis of the legend of Mpok Ris found evidence of denotation, connotation, and myth, according to the findings. Mpok Ris legend features some character education principles, including the virtues of hard labor, inventiveness and independence as well as the values of loyalty to one's homeland, friendly/communicativeness and duty to the community